Enhanced bioelectrochemical degradation of Thiabendazole using biostimulated Tunisian hypersaline sediments: kinetics, efficiency, and microbial community shifts - Nesrine Saidi; Benjamin Erable; Luc Etchevery; Ameur Cherif; Habib Chouchane (Frontiers in Microbiology)
Thiabendazole (TBZ), a recalcitrant fungicide, is frequently applied in postharvest fruit treatment and generates significant volumes of industrial wastewater (WW) that conventional treatment plants cannot handle. This explores a bioelectrochemical system (BES) for TBZ degradation using Tunisian hypersaline sediments (THSs) as inoculum. Four sets of BES, along with biological controls, were tested using THS subjected to different levels of TBZ biostimulation. Sediments underwent one, two, or three biostimulation phases with increasing TBZ concentrations (0, 10, 100, and 300 mg kg−1). Potentiostatic control was applied to BES, polarized at 0.1 V vs. saturated calomel reference electrode (SCE), with a carbon felt working electrode (72 cm2 L−1) and maintained at 25°C. While current production was very low, sediments biostimulated with 100 mg kg−1 kg TBZ produced the highest current density (3.2 mA m−2), a 5-fold increase over untreated sediments (0.6 mA m−2). GC-FID analysis showed >99% TBZ degradation in all reactors. The TBZ half-elimination time from 27 days with biological treatments to 19 days in BES and further to 6 days following biostimulation. Bacterial analysis revealed a substantial microbial community shift after biostimulation, with a reduction in Bacillota (−64%) and an increase in Proteobacteria (+62%), dominated by Pseudomonas (45%) and Marinobacter (16%). These findings provide insight into the selective potential of biostimulation cycles to enhance microbial community composition and improve BES performance for TBZ wastewater treatment.